Extraction of Rice Bran Oil from Rice Bran by Supercritical Carbon Dioxide - Van Khanh, Nguyen; Thanh Hai, Nguyen; Thi Huyen, Nguyen; Anh Hoang, Dao; Quoc Thinh, Tran (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2021)
Rice bran is an important source of nutrients that have many good bioactive compounds. This study examined the extraction of bran rice oil using supercritical carbon dioxide. Free fatty acids contained in bran rice were stabilized at 5.25% for 8 months by fluid bed dryer equipment. Supercritical carbon dioxide extraction of rice bran oil at pressure of 400 bar, temperature of 60 o C, CO 2 flow rate of 20 g/min for 120 minutes yielded 14.84% oil. The concentration of γ-oryzanol in rice bran oil extracted by supercritical carbon dioxide (0.50%) was higher than in rice bran oil derived from hexane Soxhlet extraction (0.42%). The effect of pressure and temperature on extraction yield and the concentration of γ-oryzanol contained in rice bran oil was observed. Keywords Rice bran, rice bran oil, γ-oryzanol, free fatty acid, supercritical carbon dioxide. References [1] A. A. Wani, P. Singh, M. A. Shah, U. S. Weisz, K. Gul, I. A. Wani, Rice Starch Diversity: Effects on Structural, Morphological, Thermal, and Physicochemical Properties - A Review, Comprehensive Reviews in Food Science and Food Safety, Vol. 11, No. 5, 2012, pp. 417-436, https://doi.org/10.1111/j.1541-4337.2012.00193.x. [2] K. Gul, B. Yousuf, A. K. Singh, P. Singh, A. A. Wani, Rice Bran: Nutritional Values and Its Emerging Potential for Development of Functional Food - A Review, Bioactive Carbohydrates and Dietary Fibre, Vol. 6, No. 1, 2015, pp. 24-30, https://doi.org/10.1016/j.bcdf.2015.06.002. [3] G. Hua, S. Huang, S. Cao, Z. Ma, Effect of Enrichment with Hemicellulose from Rice Bran on Chemical and Functional Properties of Bread, Food Chemistry, Vol. 115, No. 3, 2009, pp. 839-842, https://doi.org/10.1016/j.foodchem.2008.12.092. [4] T. S. Shin, J. S. Godber, Changes of Endogenous Antioxidants and Fatty Acid Composition in Irradiated Rice Bran during Storage, Journal of Agricultural Food Chemistry, Vol. 44, 1996, pp. 567-573, https://doi.org/10.1021/jf950386a. [5] B. O. Juliano, P. A. Hicks, Rice Functional Properties and Rice Food Products, Food Reviews International, Vol. 12, No. 1, 1996, pp. 71-103, https://doi.org/10.1080/87559129609541068. [6] M. Ghosh, Review on Recent Trends in Rice Bran Oil Processing, J Amer Oil Chem Soc, Vol. 84, 2007, pp. 315-324, https://doi.org/10.1007/s11746-007-1047-3. [7] M. Sugano, E. Tsuji, Rice Bran Oil and Cholesterol Metabolism, Journal of Nutrition, Vol. 127, No. 3, 1997, pp. 521-524, https://doi.org/10.1093/jn/127.3.521S. [8] G. S. Seetharamaiah, N. Chandrasekhara, Studies on Hypocholesterolemic Activity of Rice Bran Oil, Atherosclerosis, Vol. 78, No. 2-3, 1989, pp. 219-223, https://doi.org/10.1016/0021-9150(89)90226-8. [9] J. K. Duve, P. J. White, Extraction and Identification of Antioxidants in Oats, Journal of American Oil Chemists Society, Vol. 68, No. 6, 1991, pp. 365-37, https://doi.org/10.1007/BF02663751. [10] L. Xu, X. Zhan, Z. Zeng, R. Chen, H. Li, T. Xie, S. Wang, Recent Advances on Supercritical Fluid Extraction of Essential Oils, African Journal of Pharmacy and Pharmacology, Vol. 5, No. 9, 2011, pp. 1196-1211, https://doi.org/10.5897/AJPP11.228. [11] C. R. Chen, C. H. Wang, L. Y. Wang, Z. H. Hong, S. H. Chen, W. J. Ho, C. M. J. Chang, Supercritical Carbon Dioxide Extraction and Deacidification of Rice Bran Oil, J. of Supercritical Fluids, Vol. 45, No. 3, 2008, pp. 322-331, https://doi.org/10.1016/j.supflu.2008.01.006. [12] K. Tomita, S. Machmudah, Wahyudiono, R. Fukuzato, H. Kanda, A. T. Quitain, M. Sasaki, M. Goto, Extraction of Rice Bran Oil by Supercritical Carbon Dioxide and Solubility Consideration, Separation and Purification Technology, Vol. 125, No. 7, 2014, pp. 319-325, http://dx.doi.org/10.1016/j.seppur.2014.02.008. [13] F. Malekian, R. M. Rao, W. Prinyawiwatkul, W. E. Marshall, M. Windhauser, M. Ahmedna, Lipase and Lipoxygenase Activity, Functionality, and Nutrient Losses in Rice Bran During Storage, Bull. La. Agric. Exp. Stn. LSU Agric. Cent., Vol. 870, 2000, pp. 1-68. [14] S. Akter, M. Ahiduzzaman, Effect of Storage Life of Rice Bran on the Quality of Oil, Journal of Food and Nutrition Sciences, Vol. 5, No. 1, 2017, pp. 11-15, https://doi.org/10.11648/j.jfns.20170501.12. [15] H. R. Sharma, G. S. Chauhan, K. Agrawal, Physico-Chemical Characteristics of Rice Bran Processed by Dry Heating and Extrusion Cooking, International Journal of Food Properties, Vol. 7, No. 3, 2004, pp. 603-614, https://doi.org/10.1081/JFP-200033047. [16] N. R. Lakkakula, M. Lima, T. Walker, Rice Bran Stabilization and Rice Bran Oil Extraction using Ohmic Heating, Bioresource Technology, Vol. 92, No. 2, 2004, pp. 157-161, https://doi.org/10.1016/j.biortech.2003.08.010. [17] D. Martin, J. S. Gober, G. Selhako, L. Verma, J. H. Wells, Optimizing Rice Bran Stabilization by Extrusion Cooking, Lousiana Agraculture, Vol. 30, 1993, pp. 13. [18] R. N. Sayre, R. M. Saunders, R. V. Enochian, W. G. Shultz, E. C. Beagle, Review of Rice Bran Stabilization Systems with Emphasis on Extrusion Cooking, Cereal Food World, Vol. 7, 1982, pp. 317. [19] M. S. Kuk, M. K. Dowd, Supercritical CO2 Extraction of Rice Bran, J. Am. Oil Chem. Soc, Vol. 75, 1998, pp. 623-628. [20] Y. T. Chen, Y. H. Ling, An Overview of Supercritical Fluid Extraction in Chinese Herbal Medicine: from Preparation to Analysis, J. Food Drug Anal, Vol. 8, No. 4, 2000, pp. 235-247, https://doi.org/10.38212/2224-6614.2815. [21] S. R. S. Ferreira, Z. L. Nikolov, L. K. Doraiswamy, M. A. A. Meireles, A. J. Petenatee, Supercritical Fluid Extraction of Black Pepper (Piper nigrun L.) Essential Oil, J. Supercrit. Fluids, Vol. 14, No. 3, 1999, pp. 235-245. [22] A. Awasthi, R. K. Trivedi, A Review of Supercritical Carbon Dioxide Extraction of Natural Products, Chem. Eng. World, Vol. 32, 1997, pp. 65-71.